2005
DOI: 10.1021/ma050974h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ideal, Organic Nanoparticles on the Flow Properties of Linear Polymers:  Non-Einstein-like Behavior

Abstract: The effect of nanoscopic, shape persistent polystyrene (PS) nanoparticles on the rheological properties of linear PS is studied and a dramatic viscosity reduction is observed. This is an ideal blend which simplifies enthalpic interactions between the components and can be used to delineate the effect of particle size on the properties of the blends. Homogeneous blends are assured through small-angle neutron scattering (SANS) experiments which establish the absence of phase segregation (depletion flocculation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
251
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(274 citation statements)
references
References 62 publications
22
251
1
Order By: Relevance
“…A similar model system has been also studied by Zhang and Archer [14] and Sarvestani and Picu [11]. For such a system, molecular simulations [2,10] estimated that a bridging network linking neighboring nanoparticles forms once the wall-to-wall distance between nanoparticles, d w , approximated by [18] …”
Section: Terminal Relaxation Timementioning
confidence: 99%
“…A similar model system has been also studied by Zhang and Archer [14] and Sarvestani and Picu [11]. For such a system, molecular simulations [2,10] estimated that a bridging network linking neighboring nanoparticles forms once the wall-to-wall distance between nanoparticles, d w , approximated by [18] …”
Section: Terminal Relaxation Timementioning
confidence: 99%
“…4a, d). Tuteja et al [31] found a nonlinear dependence for entangled polymer melt flow through addition of nanoparticles and attributed the system zero shear viscosity and relaxation modulus decrease to lower interparticle distance than polymer chain dimension. The observed phenomenon was assigned to two mechanisms: free volume increase and chain constraint release.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 has been reported. 56,57 The storage (G') and loss (G") moduli from frequency and strain sweeps for all of the NH 2 PDMS samples with different amounts of 4DCA are collected in Figures S24 and S25 (SI section). The data show that both samples in which the COOH/NH 2 ratio is 100% are not gels: in the linear viscoelastic regions, G' remains lower than G".…”
Section: Degradation Of Trichloroethylene (Tce) In Methanol Suspensiomentioning
confidence: 99%